Risk, temptation, and efficiency in prisoner's dilemmas - Simon Gächter; Kyeongtae Lee; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
We examine the effect of payoff variations on cooperation in one-shot prisoner's dilemma games. We focus on three factors: risk, temptation, and efficiency, which we vary as orthogonal treatments. We find that temptation has the largest impact on cooperation. Temptation directly deters cooperation and indirectly harms cooperation by lowering beliefs about the opponent's cooperativeness. Efficiency indirectly affects cooperation through beliefs, but the magnitude of the effect is relatively small compared to temptation. Risk does not have a significant effect on cooperation. Our finding suggests that curbing the level of temptation is the most important way to improve cooperation in social dilemmas.
Keywords: A13; C91; 330; prisoner's dilemma; cooperation; temptation; efficiency; risk